DAMPAK LINKUNGAN TERHADAP PENCEMARAN LAUT DI PESISIR UTARA PULAU BINTAN SELAMA MUSIM ANGIN UTARA - gembong satria negara (JURNAL SAINS DAN TEKNOLOGI MARITIM, 2020)
The north coast of Bintan Island is faces directly to the South China Sea. It is a traffic point for commercial vessels that will enter and exit the Singapore Strait. Nowadays, the Singapore Strait is one of the busiest straits in the world. Every day hundreds of ships will cross this strait. This condition makes the north coast of Batam Island and Bintan Island are vulnerable to environmental pollution caused by the activities of these commercial vessels.One of the things that attracts awareness and continues to happen is sea pollution. It happens on the north coast of Bintan Island. It is always occurs during the North East Monsoon. A lot of waste oil sludge will easily found along the north coast of Bintan Island. It suspected that the waste originated from ships passing the north sea of Bintan Island. Writing is based on a literature review and discuss a case study on the environmental impact of pollution of the sea in the northern coast of the island of Bintan.Keywords : Sea, Waste, Sludge, Monsoon, EnvironmentPesisir utara Pulau Bintan merupakan daratan yang berhadapan langsung dengan laut cina selatan yang menjadi muara lalulintas kapal kapal niaga yang akan masuk dan keluar dari selat Singapura. Saat ini selat Singapura adalah salah satu selat tersibuk didunia, setiap harinya ratusan kapal akan melintasi selat ini. Kondisi inilah yang menjadikan pesisir utara Pulau Batam dan Pulau Bintan menjadi sangat rentan terhadap pencemaran lingkungan yang disebabkan dari aktivitas kapal kapal niaga tersebut. Salah satu hal yang menarik perhatian dan masih terus terjadi adalah pencemaran laut di pesisir utara Pulau Bintan selalunya terjadi pada saat musim angin utara (North East Monsoon). Limbah minyak kotor (sludge) akan mudah ditemui disepanjang pesisir utara pantai Pulau Bintan. Patut diduga limbah tersebut berasal dari kapal kapal yang melintas di laut sebelah utara Pulau Bintan. Penulusan ini didasarkan pada studi literatur dan study kasus yang membahas mengenai dampak lingkungan terhadap pencemaran laut di pesisir utara pulau Bintan.Kata kunci : Laut, Limbah, Sludge, Monsoon, Lingkungan